Metabolic reprogramming in esophageal squamous cell carcinoma - Wang, Ziyi; Sun, Xiangyu; Li, Zehui; Yu, Huidong; Li, Wenya; Xu, Yan (Frontiers in Pharmacology, 2024)
Esophageal squamous cell carcinoma (ESCC) is a malignancy with high incidence in China.Due to the lack of effective molecular targets, the prognosis of ESCC patients is poor. It is urgent to explore the pathogenesis of ESCC to identify promising therapeutic targets.Metabolic reprogramming is an emerging hallmark of ESCC, providing a novel perspective for revealing the biological features of ESCC. In the hypoxic and nutrient-limited tumor microenvironment, ESCC cells have to reprogram their metabolic phenotypes to fulfill the demands of bioenergetics, biosynthesis and redox homostasis of ESCC cells. In this review, we summarized the metabolic reprogramming of ESCC cells that involves glucose metabolism, lipid metabolism, and amino acid metabolism and explore how reprogrammed metabolism provokes novel opportunities for biomarkers and potential therapeutic targets of ESCC.